Pengaruh Marketing Mix Terhadap Perilaku Konsumen Generasi Z Dalam Pembelian Fashion Muslim - Kamil, Muhammad Raihan; Harahap, Isnaini; Nasution, Juliana (Journal of Business and Economics Research (JBE), 2025)
This study aims to determine the effect of marketing mix on generation Z consumer behavior in purchasing Rabbani Medan Muslim fashion. The population in this study were all consumers of Rabbani Medan stores totaling 400 people while the sample in this study were consumers who were generation Z in Rabbani Medan stores totaling 100 people. This study uses quantitative methods with data collection using the Likert scale method. The results of this study show that product, price, place, promotion and employees have a significant influence on the purchasing decision of Rabbani Muslim fashion. This means that the behavior of generation Z towards the Muslim fashion industry which is currently growing quite rapidly in Indonesia is increasingly positive from day to day. These results show that F count> F table (8.002> 2.20) with a significance level of 0.028 <0.05. So it can be concluded that the behavior of generation Z consumers has an influence on fashion purchasing decisions at Rabbani Medan.